1980
DOI: 10.1111/j.1469-8137.1980.tb00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Hawkmoth Behaviour and Flower Adaptation Reducing Self Pollination in Two Liliiflorae

Abstract: Summary In experiments with models and a Petunia cultivar a hawkmoth makes its initial approach at about the same level as the flower. In Lilium martagon L., after flower opening, the style curves towards the direction of maximum light intensity. A hawkmoth comes into contact with the stigma at the beginning of its visit. Thereafter, while drinking from the individual nectaries on each petal, the visitor picks up pollen from the anther in front of the petals. During the initial approach to Crinum jagns (Thomp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 5 publications
1
19
0
1
Order By: Relevance
“…The lack of this counterturning in the flight paths recorded in the present study is most likely due to the lack of a uniform airflow in our arena, where, instead, the local concentration gradients and the plume fragments provide information about the location of the odour source (Fraenkel and Gunn, 1961). Straight flight in moths has also been reported previously from flight conditions with homogeneous or turbulent odour plumes (Mafra-Neto and Cardé, 1994), as well as in still air (Brantjes, 1978;Brantjes and Bos, 1980). When approaching the multimodal target -which was both clearly visible and carried an odour -the moths turned directly towards it (Fig.5) and were also able to locate it from any visual angle (Fig.7).…”
Section: Discussionsupporting
confidence: 80%
“…The lack of this counterturning in the flight paths recorded in the present study is most likely due to the lack of a uniform airflow in our arena, where, instead, the local concentration gradients and the plume fragments provide information about the location of the odour source (Fraenkel and Gunn, 1961). Straight flight in moths has also been reported previously from flight conditions with homogeneous or turbulent odour plumes (Mafra-Neto and Cardé, 1994), as well as in still air (Brantjes, 1978;Brantjes and Bos, 1980). When approaching the multimodal target -which was both clearly visible and carried an odour -the moths turned directly towards it (Fig.5) and were also able to locate it from any visual angle (Fig.7).…”
Section: Discussionsupporting
confidence: 80%
“…Further investigation of the influence of mechanoreception on probing behavior led to Experiment 2, in which we found that corolla grooves positively affect the handling performance when they converge at the nectary and negatively affect it when they are incorrectly oriented (Fig.·5). This suggests that three-dimensional features have a hierarchical precedence on nectar-searching behavior at the flower handling scale as proposed by Brantjes and Bos (Brantjes and Bos, 1980). At this level, the spatial resolution of M. sexta's eyes does not allow for accurate feedback about proboscis position (A.…”
Section: Vision and Mechanoreception During Flower Probingmentioning
confidence: 98%
“…1E), Polemoniaceae (Grant & Grant 1965), and others. Brantjes & Bos (1980) provided three detailed examples of what we describe as approach herkogamy, all in species pollinated by hawkmoths:…”
Section: Approach Herkogamymentioning
confidence: 99%